ByzRev 04.2022.011: Dorotei Getov, A Catalogue of the Greek Manuscripts in the National Library “Sts. Cyril and Methodius”, Sofia.: Transmission des Textes: Catalogues. Turnhout: Brepols 2019. - Afentoulidou, Eirini (The Byzantine Review, 2022)
Dorotei Getov, A Catalogue of the Greek Manuscripts in the National Library “Sts. Cyril and Methodius”, Sofia. Transmission des Textes: Catalogues. Turnhout: Brepols 2019. XX, 335 S., 175 Taf. – ISBN 978-2-503-58612-0 (€ 95.00)